Effects of passive and active joint compliance in quadrupedal locomotion. (3rd August 2018) - Mutlu, M.; Hauser, S.; Bernardino, A.; Ijspeert, A. J.
ABSTRACT: Compliance of the body has a crucial role on locomotion performance. The levels and the distribution of compliance should be well tuned to obtain efficient gait. The leg stiffness changes significantly even during different phases of a single gait cycle. This paper presents an experimental study on different passive and active limb compliance configurations. Each configuration is tested on flat, rough and inclined-rough surfaces, to analyze locomotion performance in diverse conditions. As the active compliance mechanism, Tegotae-based control is selected. Even though active compliance is not its primary use, we show that the Tegotae rule presents intriguing features that have potential to boost gait performance in various scenarios. GRAPHICAL ABSTRACT: